2014
DOI: 10.1371/currents.hd.a3ad1a381ab1eed117675145318c9a80
|View full text |Cite
|
Sign up to set email alerts
|

Trinucleotide repeats and haplotypes at the Huntingtin locus in an Indian sample overlaps with European haplogroup A

Abstract: Huntington's disease (HD), an autosomal dominant neurodegenerative syndrome, has a world-wide distribution. An estimated 2.5-10/100,000 people of European ancestry are affected with HD, while the Asian populations have lower prevalence (0.6-3.8/100,000). The epidemiology of HD is not well described in India, and the distribution of the pathogenic CAG expansion, and the associated haplotype, in this population needs to be better understood. This study demonstrates a distribution of CAG repeats, at the HTT locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A conservative estimate of about 75,000 HD patients in India (10,14) would indicate almost a million at risk. As about a quarter of the patients eligible for the study could not be contacted, this data possibly under-represents the overall morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A conservative estimate of about 75,000 HD patients in India (10,14) would indicate almost a million at risk. As about a quarter of the patients eligible for the study could not be contacted, this data possibly under-represents the overall morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the number of HD cases is being noted lately, with wider availability of genetic diagnostics. It is quite likely that the prevalence rate will be similar to that in European populations with similar haplotype (14) (approximately 3-5/1,00,000 population; or about 40,000-70,000 individuals with HD in India).…”
Section: Introductionmentioning
confidence: 97%
“…Historically, symptoms of chorea had been observed by many physicians (Lanska, 2010 ), while George Huntington portrayed the clinical symptoms and provided the evidence for the hereditary nature of HD in 1872 (Huntington, 1872 ; Lanska, 2000 ). Since then, an enormous scientific progress has been made in understanding the biochemical, molecular genetics and pathological basis of HD worldwide (Wexler et al, 2004 ; Bates, 2005 ; Moily et al, 2014 ). In 1983, the HD Collaborative Research Group, under the direction of Nancy Wexler, successfully mapped the defective gene responsible for HD to chromosome 4p16.3 (Gusella et al, 1983 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, several lines of experimental evidence of gene knockout paradigms suggested that the expression of WT HD gene is indispensable for embryogenesis, vesicular trafficking, synaptic plasticity and neuroprotection (Duyao et al, 1995 ; Dragatsis et al, 2000 ; Reiner et al, 2003 ). The unstable CAG repeat expansion of more than 35–39 in the HD gene is translated into polyglutamine (polyQ) stretches in the huntingtin protein (Bates, 2003 ; Cornett et al, 2005 ; Moily et al, 2014 ). The abnormal polyQ repeat sequence is known to cause misfolding and aggregation of the huntingtin protein (DiFiglia et al, 1997 ; Bates, 2005 ; Poirier et al, 2005 ) leading to the selective degeneration of medium spiny neurons (MSNs) in the striatum and onset of the disease (Graveland et al, 1985 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of incidence of HD is considerably higher in the Caucasian population than the Asian population. While an estimate shows the prevalence and increasing trend of HD in Western Europe, Australia, North America, and the United Kingdom, India represents a large number of total HD cases in Asia [ 11 , 12 ]. Single nucleotide polymorphism (SNP) at the HTT locus in association with the genetic diversity, lifestyle, food, and environmental factors is presumed to be the reasons for the variations in the frequency of HD among the human population [ 13 ].…”
Section: Introductionmentioning
confidence: 99%